An Analysis on Understanding intercultural differences and relations and the role of ICTs - Papadaki, Aggeliki; Karagianni, Eleni; Driga, Anna Maria (Eximia, 2023)
The purpose of this article is to describe a critical incident based on Wight’s description. In the first part, there is a presentation and description of the critical incident that took place in Barcelona, Spain. In the second part, there is an analysis of the possible reasons that led to the particular miscommunication. In the third part, there is reflection, followed by a brief conclusion summarizing the key concepts mentioned earlier.